2020
DOI: 10.1186/s12916-020-01594-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of testosterone in chronic kidney disease and kidney function in men and women: a bi-directional Mendelian randomization study in the UK Biobank

Abstract: Background: Chronic kidney disease (CKD) has an apparent sex disparity, with a more rapid progress in men than in women. Whether the well-established sex-specific evolutionary biology trade-off between reproduction and longevity might inform CKD has not previously been considered. Relevant evidence from randomized controlled trials (RCTs) is not available. Methods: We used a bi-directional Mendelian randomization study to obtain unconfounded estimates using the UK Biobank. Single nucleotide polymorphisms (SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 60 publications
0
40
0
2
Order By: Relevance
“…Genetic associations with testosterone in this study were adjusted for genotyping chip/release of genetic data, age at baseline, fasting time and ten genetically derived principal components ( Ruth et al, 2020 ). We used all 125 genetic variants given for bioavailable testosterone, hereafter testosterone, in men and all 254 genetic variants given for testosterone in women, as previously ( Zhao and Schooling, 2020 ), because these had little correlation with sex hormone binding globulin (0.05 in men and 0.06 in women) ( Ruth et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic associations with testosterone in this study were adjusted for genotyping chip/release of genetic data, age at baseline, fasting time and ten genetically derived principal components ( Ruth et al, 2020 ). We used all 125 genetic variants given for bioavailable testosterone, hereafter testosterone, in men and all 254 genetic variants given for testosterone in women, as previously ( Zhao and Schooling, 2020 ), because these had little correlation with sex hormone binding globulin (0.05 in men and 0.06 in women) ( Ruth et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of the UK biobank provided a great contribution to the prognostic research in CKD. For example, genetically predicted testosterone and fasting insulin, with the latter being an expression of insulin resistance, were found to be associated with CKD and worse kidney function in men, thus highlighting the possible reasons for discrepancy in CKD prevalence and CKD progression among men and women [84,85]. Intriguingly, a genome-wide association study of UK biobank showed that albumin-to-creatinine ratio (ACR) is dependent on multiple pathways and that an ACR genetic risk score may improve the prediction of hypertension and stroke [86].…”
Section: Prognostic Role Of Proteomics Metabolomics and Genomicsmentioning
confidence: 99%
“…However, an RCT of dual blockade of RAAS with ACE inhibitors and ARB did not exhibit more benefits for kidney function than monotherapy [ 29 ], raising the possibility that other pathways might exist. Notably, CKD has an apparent sex disparity, and testosterone has been recognized as a causal factor explaining, or partly explaining, unfavorable kidney function in men [ 30 , 31 ]. ACE inhibitors and CCB may also play a role by modulating sex hormones.…”
Section: Discussionmentioning
confidence: 99%